2016
DOI: 10.1007/s12185-016-2130-z
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the safety and efficacy of ruxolitinib in a multicenter, open-label study in Japanese patients with myelofibrosis

Abstract: Ruxolitinib is a potent JAK1/JAK2 inhibitor that has demonstrated durable improvements in splenomegaly, symptoms, and overall survival in controlled clinical trials in patients with myelofibrosis. The single-arm study reported here was initiated to collect further safety and efficacy data in Japanese patients with myelofibrosis and is the largest study of ruxolitinib in this population. The primary objective was to assess safety. Secondary endpoints included changes in spleen size and patient-reported outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
10
3
Order By: Relevance
“…Only one case of herpes zoster reactivation has been described, whereas no cases of tuberculosis were reported. In a study of ruxolitinib in Japanese patients with MF, herpes zoster infections were reported in 2 patients (3.9%), pneumonia in 4 (8%), urinary tract infection in 1 (2%) and sepsis in 1 (2%) . Finally, in a very small study of 10 patients in Taiwan, one hepatitis B reactivation was reported …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Only one case of herpes zoster reactivation has been described, whereas no cases of tuberculosis were reported. In a study of ruxolitinib in Japanese patients with MF, herpes zoster infections were reported in 2 patients (3.9%), pneumonia in 4 (8%), urinary tract infection in 1 (2%) and sepsis in 1 (2%) . Finally, in a very small study of 10 patients in Taiwan, one hepatitis B reactivation was reported …”
Section: Resultsmentioning
confidence: 97%
“…Eight papers were excluded for the following reasons: pooled analysis ( n = 1), follow‐up of phase I or II trial ( n = 1), sub‐analyses ( n = 2), data on extension phase study with a shorter follow‐up ( n = 2), redundant publications ( n = 2). Five phase III RCTs (3 phase IIIa with their most recently published extended phase (750 patients) and 2 phase IIIb RCTs (283 patients)), 6 phase IV studies (1524 patients) and 28 case report publications (31 patients, of whom 4 were included also in phase III studies and 1 in phase IV study) were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The change in infectious rate is not always obvious. 15,16 We note that the incidence of herpes zoster infection is significantly increased in the rux group, while other infections are not. 2 Revealing the same outcome, a systematic review suggested a clinical relevance to the risk.…”
Section: Dovepressmentioning
confidence: 77%
“…Based on these findings, the patient was diagnosed with post-PV myelofibrosis. She was enrolled in an AJP-01 study ( 8 ), and treatment with ruxolitinib (10 mg, b.i.d.) was initiated according to the protocol.…”
Section: Case Reportmentioning
confidence: 99%